A Slice of heaven for God's children : community for the orphaned children Bustos, Bulacan - Placido, Fatima J. (Manila : National University, 2016)
The motivation for this thesis is an attempt to improve the way of living of an orphan to a typical orphanage. This project specifically focuses on the question, in what ways do architecture affect human behaviour and development and the right environment theses children needed.
Chapter 1. The Problem and it's settings -- Chapter 2. Research Methodology -- Chapter 3. Terms and Reference -- Chapter 4. Data Gathering, Collection and Analysis of Data -- Chapter 5. Design Framework -- Chapter 6. Translations -- Bibliography -- Appendices
Includes bibliographical references.